Evaluation of changing the pattern of CTRP5 and inflammatory markers levels in patients with coronary artery disease and type 2 diabetes mellitus. (4th July 2022) - Moradi, Nariman; Fadaei, Reza; Rashidbeygi, Elaheh; Bagheri Kargasheh, Fatemeh; Malek, Mojtaba; Shokoohi Nahrkhalaji, Abolfazl; Fallah, Soudabeh
Abstract: Purpose: It has recently found that adipokines, play a numerous functional roles in inflammation, lipids and glucose metabolism and in the pathogenically conditions such as atherosclerosis and insulin resistance. Therefore, for the first time we aimed the present study to evaluating serum levels of CTRP5 and inflammatory cytokines patients with CAD and T2DM in comparison with controls. Methods: This study was done on 44 patients with CAD, 45 type 2 diabetes mellitus (T2DM), 41 CAD + T2DM and 41 controls. Serum levels of TNF-α, IL-6, MCP-1 and CTRP5 were investigated by ELISA method. Results: The CTRP5 levels of all patients groups were lower in comparison with control group. There was a significant negative relationship between CTRP5 levels and cytokines concentration in the studied patients. Conclusions: Our findings suggested a potential role of CTRP5 in inflammatory process of underlying atherosclerosis and diabetes; however, more studies are needed to support these finding.